Method for manufacturing liquid metal microparticles with high aspect ratio and liquid metal microparticles manufactured thereof
Patent Information
- Application Number
- KR1020230078260
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2043-06-19
Smart Images

Figure 112023067148410-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing liquid metal microparticles of high-grade equipment and liquid metal microparticles manufactured therefrom. Background Technology
[0002] Various methods are being attempted to fabricate high-functional and high-performance composites by incorporating microparticles that add diverse functionalities to the material. In particular, reinforcing materials processed into particle form are easy to disperse uniformly throughout the composite material and exhibit excellent effects even in small amounts. Therefore, to meet user demands in various application fields, active research is being conducted on processes that control particle shape to achieve enhanced performance with smaller quantities.
[0003] The particle molding process can be classified into passive methods and active methods depending on the presence or absence of body force.
[0004] Passive methods refer to methods of forming particles by surface forces generated at the interface of liquid particles before solidification, and particle fabrication techniques for solid equipment are mainly reported through solvent evaporation and diffusion methods and micro-molding.
[0005] The solvent evaporation and diffusion method controls particle formation by precisely inducing and controlling the self-assembly of liquid block copolymers. By controlling the solvent evaporation rate, lamellae are formed in the vertical direction, enabling the fabrication of particles with a stable ellipsoidal structure. However, the solvent evaporation and diffusion method is applicable only at very small nanoscales, making the fabrication of large microparticles difficult; furthermore, it presents a problem of low manufacturability for mass production due to the continuous consumption of solvent.
[0006] Particle molding by micro-molding can produce simple, accurate, and precise three-dimensional microstructures by filling a mold with a curable fluid and then extracting it. Additionally, by using a solvent with excellent wettability to create a gap between the mold and the filled polymer fluid, particles can be recovered with minimal external force. However, this method requires an additional precise cleaning process for mold use, and its application to expensive liquid metals is limited due to the large amount of material lost as only a portion of the sample is used for fabrication.
[0007] Active methods refer to a method of controlling particle shape by applying external energy, where additional energy regulates force balance and stability at the interface. Active methods primarily include mechanical, electrical, magnetic, and optical methods.
[0008] Among them, mechanical methods allow for precise control of particle shape and have excellent scalability, enabling the production of various particle shapes with slight adjustments to process variables. However, this method also has disadvantages such as high production costs, limitations on particle size, low production volume, and limitations on three-dimensional control of particles.
[0009] Liquid metals not only possess high electrical and thermal conductivity but also exhibit strong mechanical rigidity in the solid phase compared to polymers. Additionally, their low melting points facilitate easy molding into particulate forms. However, because liquid metals exhibit stronger intermolecular forces than polymers, liquid particles strongly aggregate into spherical shapes at the micro-scale, making it very challenging to control their particle shape. Furthermore, existing processes for controlling liquid metal particle shapes involve various chemical treatments, posing risks associated with environmental pollution and process hazards.
[0010] Therefore, there is a need for a method to manufacture liquid metal microparticles using high-tech equipment that is environmentally friendly, cost-effective, simple, and capable of mass production, unlike existing liquid metal particle shape control processes. Prior art literature
[0011] Republic of Korea Public Notice No. 10-2012-0099164 (September 7, 2012) The problem to be solved
[0012] The problem that the present invention aims to solve is to provide a method for manufacturing liquid metal microparticles using high-tech equipment that is environmentally friendly, cost-effective, simple to process, and capable of mass production, as well as liquid metal microparticles manufactured therefrom.
[0013] However, the problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0014] According to one aspect of the present invention, a method for producing liquid metal microparticles for high-strength equipment is provided, comprising the steps of: producing a calcium alginate filament containing liquid metal microparticles; stretching the calcium alginate filament in hot water to produce liquid metal microparticles for high-strength equipment; and decomposing the stretched calcium alginate filament to obtain liquid metal microparticles for high-strength equipment.
[0015] In addition, according to another aspect of the present invention, a liquid metal microparticle of high aspect ratio having an aspect ratio of 2 to 10 is provided, which is manufactured by the above manufacturing method. Effects of the invention
[0016] A method for manufacturing liquid metal microparticles of high-tech equipment according to one embodiment of the present invention is environmentally friendly, inexpensive, simple in process, and capable of mass production.
[0017] In addition, the liquid metal microparticles of the high-tech equipment according to one embodiment of the present invention may have excellent thermal and electrical conductivity.
[0018] However, the effects of the present invention are not limited to the effects described above and may be extended in various ways without departing from the spirit and scope of the present invention. Brief explanation of the drawing
[0019] Figure 1 is a schematic diagram showing a method for manufacturing Fields metal microparticles of high-tech equipment. Figure 2 shows Fields metal microparticles manufactured according to the method for manufacturing Fields metal microparticles of high-tech equipment. Figure 2a is a spherical Fields metal microparticle, Figure 2b is a stretched calcium alginate filament containing stretched Fields metal microparticles, and Figure 2c is a Fields metal microparticle of high-tech equipment. Figure 3 shows the secant tensile modulus of calcium alginate filaments according to the concentration of sodium alginate solution. Figure 4 shows the secant tensile modulus of calcium alginate filaments according to the concentration of the calcium chloride solution. Figure 5 shows the results of the thermal conductivity evaluation of spherical Fields metal microparticles and Fields metal microparticles of high-tech equipment. Specific details for implementing the invention
[0020] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0021] Throughout this specification, the unit “wt.%” indicates the concentration of a solution, specifically the content of a solute in a solution. For example, a sodium alginate solution with a concentration of 3 wt.% may contain 3 wt.% sodium alginate in the sodium alginate solution.
[0022] Throughout this specification, the term “liquid metal” means a metal having a melting point of 35°C to 90°C and may be a fusible alloy composed of one or more metals. For example, it may be Field's metal having a melting point of 62°C and composed of bismuth (Bi), tin (Sn), and indium (in).
[0023] Throughout this specification, the term "slenderness ratio" refers to the value obtained by dividing the long axis (major axis) of an ellipsoid by the short axis (minor axis), and the larger the slenderness ratio, the more elongated the shape of the ellipsoid may be.
[0024] The present invention will be described in more detail below.
[0025] One embodiment of the present invention provides a method for manufacturing liquid metal microparticles for high-strength equipment, comprising: a step of manufacturing a calcium alginate filament containing liquid metal microparticles; a step of stretching the calcium alginate filament in hot water to manufacture liquid metal microparticles for high-strength equipment; and a step of decomposing the stretched calcium alginate filament to obtain liquid metal microparticles for high-strength equipment.
[0026] According to one embodiment of the present invention, the liquid metal may have a melting point of 35°C to 90°C. When the melting point of the liquid metal is within the aforementioned range, the liquid metal exists in a liquid state during the step of manufacturing liquid metal microparticles of a high-strength device by stretching a calcium alginate filament in hot water, so the liquid metal microparticles of a high-strength device can be easily manufactured.
[0027] According to one embodiment of the present invention, the liquid metal may be Cerrolow 117, Cerrolow 136, Field's metal, Wood's metal, or Cerrosafe. Specifically, the melting point of Cerrolow 177 is 47.2 °C, the melting point of Cerrolow 136 is 58 °C, the melting point of Field's metal is 62 °C, the melting point of Wood's metal is 70 °C, and the melting point of Cerrosafe is 74 °C. Therefore, in the step of manufacturing liquid metal microparticles for high-performance equipment by stretching a calcium alginate filament in hot water, the liquid metal exists in a liquid state, so the liquid metal microparticles for high-performance equipment can be easily manufactured.
[0028] According to one embodiment of the present invention, the temperature of the hot water may be higher than the melting point of the liquid metal. Specifically, the temperature of the hot water may be 50°C to 95°C and may vary depending on the type of liquid metal. When the temperature of the hot water is higher than the melting point of the liquid metal, the liquid metal exists in a liquid state during the step of manufacturing liquid metal microparticles of a solid metal device by stretching a calcium alginate filament in the hot water, so the liquid metal microparticles of a solid metal device can be easily manufactured.
[0029] According to one embodiment of the present invention, the step of stretching the calcium alginate filament in hot water to produce liquid metal microparticles of solid state equipment can produce liquid metal microparticles of solid state equipment and cool the hot water to convert the liquid metal microparticles of solid state equipment into a solid state.
[0030] According to one embodiment of the present invention, the step of manufacturing the calcium alginate filament may involve extruding a sodium alginate solution containing liquid metal microparticles into a calcium chloride solution. Since the calcium alginate filament is not mixed with the liquid metal in a liquid state, it is possible to maintain the shape of the liquid metal in a liquid state. In addition, in the step of manufacturing the liquid metal microparticles of a high-strength device by stretching the calcium alginate filament in hot water, the tensile force is transferred to the liquid metal microparticles in a liquid state as the calcium alginate filament is stretched, thereby facilitating the manufacturing of the liquid metal microparticles of a high-strength device.
[0031] According to one embodiment of the present invention, the concentration of the sodium alginate solution may be 3 wt.% to 5 wt.%. Specifically, the content of the sodium alginate solution may be 3 wt.% to 5 wt.%, 3.5 wt.% to 5 wt.%, 3 wt.% to 4.5 wt.%, or 3.5 wt.% to 4.5 wt.% with respect to 100 wt.% of the sodium alginate solution. When the concentration of the sodium alginate solution is within the aforementioned range, the calcium alginate filament does not break when stretched, allowing for easy production of liquid metal microparticles for high-performance equipment. Furthermore, when the concentration of the sodium alginate solution is higher than the aforementioned range, voids may occur during the production of the calcium alginate filament, weakening the calcium alginate filament and causing it to break when stretched.
[0032] According to one embodiment of the present invention, the concentration of the calcium chloride solution may be 1 wt.% to 10 wt.%. Specifically, the calcium chloride content may be 1 wt.% to 10 wt.%, 3 wt.% to 10 wt.%, 1 wt.% to 8 wt.%, 3 wt.% to 8 wt.%, 1 wt.% to 5 wt.%, or 3 wt.% to 5 wt.% with respect to 100 wt.% of the calcium chloride solution. When the concentration of the calcium chloride solution is within the aforementioned range, the calcium alginate filament does not break when stretched, so liquid metal microparticles for high-performance equipment can be easily manufactured.
[0033] According to one embodiment of the present invention, the step of manufacturing liquid metal microparticles of the solid metal equipment may be to perform tensiles at a speed of 10 mm / s to 600 mm / s. Specifically, the tensile speed may be 10 mm / s to 600 mm / s, 10 mm / s to 300 mm / s, 10 mm / s to 100 mm / s, 10 mm / s to 50 mm / s, 20 mm / s to 500 mm / s, 20 mm / s to 350 mm / s, 20 mm / s to 200 mm / s, 20 mm / s to 75 mm / s, or 20 mm / s to 40 mm / s. When the tensile speed is within the aforementioned range, the calcium alginate filament is not damaged, and liquid metal microparticles of the solid metal equipment can be easily manufactured.
[0034] According to one embodiment of the present invention, the step of obtaining liquid metal microparticles of the solid metal equipment may involve decomposing the stretched calcium alginate filament into sodium citrate or trisodium citrate. While most filaments other than calcium alginate can be removed by applying heat, the liquid metal according to the present invention has the problem of losing its stretched ellipsoidal shape and returning to a liquid state when heat is applied. Therefore, the present invention allows for the decomposition of calcium alginate filaments using sodium citrate or trisodium citrate, thereby enabling easy obtaining of liquid metal microparticles of the solid metal equipment.
[0035] According to one embodiment of the present invention, the method may further include a step of producing liquid metal microparticles by stirring the liquid metal in a high-temperature starch solution before the step of producing the calcium alginate filament. Additionally, the liquid metal microparticles may be produced and the high-temperature starch solution may be cooled to convert the liquid metal microparticles in a liquid state into a solid state.
[0036] The above liquid metal has strong surface tension due to strong intermolecular forces, and as a result, liquid particles strongly aggregate into spherical shapes at the micro scale, so they can be spherical.
[0037] According to one embodiment of the present invention, the high temperature starch solution may be 50°C to 95°C and may vary depending on the type of liquid metal. When the temperature of the starch solution is higher than the melting point of the liquid metal, the liquid metal exists in a liquid state, so liquid metal microparticles can be easily manufactured.
[0038] According to one embodiment of the present invention, the concentration of the starch solution may be 5 wt.% to 15 wt.%. Specifically, the starch content may be 5 wt.% to 15 wt.%, 8 wt.% to 15 wt.%, 5 wt.% to 12 wt.%, or 8 wt.% to 12 wt.% with respect to 100 wt.% of the starch solution. When the concentration of the starch solution is within the aforementioned range, the diameter of the liquid metal microparticles can be easily controlled.
[0039] According to one embodiment of the present invention, the stirring speed may be 500 rpm to 30,000 rpm. Specifically, the stirring speed may be 500 rpm to 30,000 rpm, 500 rpm to 25,000 rpm, 500 rpm to 20,000 rpm, 500 rpm to 10,000 rpm, 500 rpm to 5,000 rpm, 500 rpm to 2,000 rpm, 800 rpm to 3,000 rpm, 800 rpm to 2,500 rpm, or 800 rpm to 2,000 rpm. When the stirring speed is adjusted within the aforementioned range, the diameter of the liquid metal microparticles can be easily controlled.
[0040] According to one embodiment of the present invention, after the step of preparing liquid metal microparticles by stirring liquid metal in a high-temperature starch solution, the method may further include the step of obtaining liquid metal microparticles by decomposing starch with amylase. The present invention allows for easy obtaining of liquid metal microparticles by decomposing starch with the aforementioned amylase.
[0041] One embodiment of the present invention provides high-aspect-ratio liquid metal microparticles having an aspect ratio of 2 to 10, manufactured by the above manufacturing method. The high-aspect-ratio liquid metal microparticles may have superior thermal and electrical conductivity compared to conventional spherical liquid metal microparticles.
[0042] According to one embodiment of the present invention, the size of the liquid metal microparticles may be 1 μm to 1000 μm. Specifically, the size of the liquid metal microparticles may be 1 μm to 1000 μm, 1 μm to 900 μm, 1 μm to 800 μm, or 5 μm to 800 μm. The size of the liquid metal microparticles can be easily controlled according to the concentration of the starch solution, the concentration of the sodium alginate solution, and the stirring speed in the step of preparing liquid metal microparticles by stirring the liquid metal in the aforementioned high-temperature starch solution.
[0043] The matters mentioned in the method for manufacturing liquid metal microparticles of the high-grade equipment and the liquid metal microparticles of the high-grade equipment of the present invention apply equally unless they contradict each other.
[0044] Hereinafter, the present invention will be described in detail using examples or experimental examples to specifically explain the invention. However, the examples or experimental examples according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the examples or experimental examples described below. The examples or experimental examples in this specification are provided to more completely explain the present invention to those with average knowledge in the art.
[0045] Example 1. Preparation of Fields metal microparticles using high-tech equipment
[0046] A 10 wt.% starch solution containing Field's metal was stirred at 1000 rpm at 90 ℃ to prepare a starch solution in which spherical Field's metal microparticles with a diameter of 200 μm were dispersed. 2 wt.% amylase was added to the prepared starch solution to gelatinize the starch solution, and spherical Field's metal microparticles were obtained from the gelatinized starch solution.
[0047] The above spherical Fieldsmetal microparticles were added to a 4 wt.% sodium alginate solution and stirred at 50 rpm for 20 minutes to prepare a sodium alginate solution containing spherical Fieldsmetal microparticles. The prepared sodium alginate solution was extruded into a 5 wt.% calcium chloride solution using a syringe to produce a calcium alginate filament containing Fieldsmetal with a diameter of 3 mm, which was then solidified. Subsequently, the calcium alginate filament was stretched in 80°C hot water at a speed of 30 mm / s along the length of the filament to produce stretched Fieldsmetal microparticles. The calcium alginate filament containing the stretched Fieldsmetal microparticles was placed in a 5 wt.% trisodium citrate solution and stirred for 20 minutes to remove the calcium alginate filament, thereby obtaining high-quality Fieldsmetal microparticles.
[0048] Examples 2 to 4
[0049] Fields metal microparticles of the high-grade equipment of Examples 2 to 5 were prepared in the same manner as Example 1, except that the concentration of the starch solution, the concentration of the sodium alginate solution, and the stirring speed were controlled when preparing spherical Fields metal microparticles as shown in Table 1 below.
[0050] Concentration of starch solution (wt.%) Concentration of sodium alginate solution (wt.%) Stirring speed (rpm) Diameter (㎛) of spherical Fieldsmetal microparticles Example 1 10 wt.% 4 wt.% 1000 rpm 200 ㎛ Example 2 12 wt.% 4 wt.% 2000 rpm 50 ㎛ Example 3 8 wt.% 4 wt.% 800 rpm 800 ㎛ Example 4 10 wt.% 3 wt.% 20,000 rpm 5 ㎛
[0051] Experimental Example 1. Evaluation of characteristics according to the composition of calcium alginate filaments
[0052] The mechanical properties of calcium alginate filaments produced according to the concentrations of sodium alginate solution and calcium chloride solution were evaluated. Specifically, calcium alginate filaments were prepared with the compositions shown in Table 2 below, and the results of the secant tensile modulus (Young's modulus) of the calcium alginate filaments according to the concentration of the sodium alginate solution are shown in Figure 3. In addition, the results of the secant tensile modulus of the calcium alginate filaments according to the concentration of the calcium chloride solution are shown in Figure 4.
[0053] Concentration of sodium alginate solution (wt.%) Concentration of calcium chloride solution (wt.%) Experimental Example 1-1 3 3 Experimental Example 1-2 4 3 Experimental Example 1-3 5 3 Experimental Example 1-4 4 1 Experimental Example 1-5 4 3 Experimental Example 1-6 4 5
[0054] As shown in Figure 3, it can be seen that the secant tensile modulus increases as the concentration of the sodium alginate solution increases. In addition, it was confirmed that the concentration of the sodium alginate solution is the most appropriate concentration, as it satisfies a secant tensile modulus of 1 to 1.5, which is the level at which the filament is almost not broken during tensile testing.
[0055] Furthermore, it was confirmed that higher concentrations of sodium alginate solution have viscosity, which causes voids to form during the manufacture of calcium alginate filaments, thereby weakening the calcium alginate filaments.
[0056] As shown in Figure 4, it can be seen that the secant tensile modulus increases as the concentration of the calcium chloride solution increases, but converges at 3 wt.%. In addition, it was confirmed that the concentrations of the calcium chloride solution from 1 wt.% to 5 wt.% are appropriate, as they satisfy a secant tensile modulus of 1 to 1.5, which is the value at which the filament is almost not broken during tensile testing.
[0057] Experimental Example 2. Measurement of aspect ratio
[0058] The aspect ratio of the Fields metal microparticles of the high-quality equipment prepared in Examples 1 to 5 above was measured using ImageJ software, and the results are shown in Table 3 below.
[0059] Length of the major axis (㎛) Length of the minor axis (㎛) Three pieces of equipment Example 1 600.8825 79.36652 7.570983 Example 2 305.503 66.42814 4.599 Example 3 274.6118 90.00459 3.051087
[0060] Experimental Example 3. Evaluation of Thermal Conductivity
[0061] Thermal conductivity evaluation specimens were prepared by including spherical Fields metal microparticles prepared in the intermediate step of Example 1 and high-grade Fields metal microparticles prepared in Example 1, respectively. Specifically, a cylindrical thermal conductivity evaluation specimen having a diameter of 10 mm and a height of 1 mm was prepared by mixing a silicone elastomer with 20 vol.% of the Fields metal microparticles using a 3D-printed mold. Thermal conductivity was evaluated by placing the thermal conductivity evaluation specimen on a heat source heated to 100 ℃ and heating it, and the results are shown in Fig. 5.
[0062] Looking at Figure 5, it can be seen that the high-grade Fields metal microparticles have superior thermal conductivity compared to the spherical Fields metal microparticles.
[0063] The above detailed description is intended to illustrate and explain the present invention. Furthermore, the foregoing merely illustrates and describes preferred embodiments of the present invention, and as described above, the present invention may be used in various other combinations, modifications, and environments, and may be modified or altered within the scope of the concept of the invention disclosed herein, the scope equivalent to the foregoing disclosure, and / or the scope of the art or knowledge. Accordingly, the above detailed description of the invention is not intended to limit the present invention to the disclosed embodiments. Additionally, the appended claims should be interpreted as including other embodiments.
Claims
Claim 1 A method for manufacturing liquid metal microparticles of an aspect ratio, comprising: a step of manufacturing a calcium alginate filament containing liquid metal microparticles; a step of manufacturing liquid metal microparticles of an aspect ratio by stretching the calcium alginate filament in hot water; and a step of obtaining liquid metal microparticles of an aspect ratio by decomposing the stretched calcium alginate filament; and further comprising a step of manufacturing liquid metal microparticles by stirring the liquid metal in a high-temperature starch solution prior to the step of manufacturing the calcium alginate filament; wherein the temperature of the starch solution is 50°C to 95°C, the temperature of the hot water is higher than the melting point of the liquid metal, and the liquid metal microparticles of an aspect ratio have an aspect ratio of 2 to 10. Claim 2 A method for manufacturing liquid metal microparticles of high-quality equipment, wherein, in claim 1, the liquid metal has a melting point of 35°C to 90°C. Claim 3 A method for manufacturing liquid metal microparticles of high-quality equipment, wherein, in claim 1, the liquid metal is Cerrolow 117, Cerrolow 136, Field's metal, Wood's metal, or Cerrosafe. Claim 4 delete Claim 5 A method for manufacturing liquid metal microparticles of high-quality equipment, wherein the step of manufacturing the calcium alginate filament is to extrude a sodium alginate solution containing liquid metal microparticles into a calcium chloride solution. Claim 6 A method for manufacturing liquid metal microparticles of high-quality equipment, wherein, in claim 5, the concentration of the sodium alginate solution is 3 wt.% to 5 wt.%. Claim 7 A method for manufacturing liquid metal microparticles of high-quality equipment, wherein, in claim 5, the concentration of the calcium chloride solution is 1 wt.% to 10 wt.%. Claim 8 A method for manufacturing liquid metal microparticles of a high-strength apparatus according to claim 1, wherein the step of manufacturing the liquid metal microparticles of the high-strength apparatus is to stretch at a speed of 10 mm / s to 600 mm / s. Claim 9 A method for manufacturing liquid metal microparticles of a high-quality device, wherein, in claim 1, the step of obtaining the liquid metal microparticles of the high-quality device is to decompose the stretched calcium alginate filament into sodium citrate or trisodium citrate. Claim 10 delete Claim 11 delete Claim 12 Liquid metal microparticles of high-grade equipment manufactured by the manufacturing method of claim 1 and having a size of 1 μm or more and 1000 μm or less.
Citation Information
Patent Citations
Liquid metal micro-nano circuit and preparation method and application thereof
CN114554708A
Fabrication method of monodisperse polymer microparticle with three-dimensional structure
KR1020120099164A
Method for preparing foam metal through foaming of porous starch
CN107552795A
Multi-shape liquid metal particle and preparation method thereof
CN114054763A
